Landscapes of Mobility in Metro Manila’s Business Districts - Boquet, Yves A. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 6, 2019)
Metro Manila has witnessed the blossoming of several business districts outside its historical core. Located mostly near the EDSA ring road and South Luzon Expressway, these business districts have become powerful attractors of office workers and shopping mall patrons, hence generating heavy commuter flows. Current urban dynamics reinforce the role of these districts as engines of growth for the whole country and define Manila as a multi-centered urban region. In addition to Ermita/Malate area, five major districts of Metro Manila are identified: Makati CBD, Bonifacio Global City, Ortigas, Alabang and the new Quezon City CBD (Vertis North) that is recently developed. These districts are not just office and shopping centers but they are also spaces of transit and transfer, whose residential component is growing with upper-end high-rise condominiums. There is indeed an expanding gap between higher-end “quality” vertical living that excludes the poor and their transport mode, and the horizontal city of the poor living in slum-like areas poorly served by many transport modes. Private developers appear to play a major role in the re-shaping of the metropolitan area, both by their new “townships” currently under development and with their influence in the design of future enhancements of the metropolitan rail system.